2006
DOI: 10.1534/genetics.106.059022
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Benefits of Systemic Acquired Resistance During Hyaloperonospora parasitica Infection in Arabidopsis thaliana

Abstract: We investigated the fitness benefits of systemic acquired resistance (SAR) in Arabidopsis thaliana using a mutational and transformational genetic approach. Genetic lines were designed to differ in the genes determining resistance signaling in a common genetic background. Two mutant lines (cpr1 and cpr5) constitutively activate SAR at different points in SAR signaling, and one mutant line (npr1) has impaired SAR. The transgenic line (NPR1-H) has enhanced resistance when SAR is activated, but SAR is still induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 58 publications
3
35
0
Order By: Relevance
“…Detection of hypersensitive response-like cell death ( Figure 7D) and PR1 expression in leaves of 6-weekold plants of S5 and the naturally RPW8-expressing accession Ms-0 grown in soil in the absence of any pathogens, along with the observation that enhanced RPW8 expression leads to spontaneous cell death and reduced plant size (Xiao et al 2003) strongly supports our speculation that reduced fitness in the RPW8 transgenic lines was due to RPW8-expression-triggered constitutive activation of an SA-dependent defense pathway under certain environmental conditions. This is consistent with the recent observations that constitutive activation of the SA-dependent defenses in several A. thaliana mutants incurred fitness costs in the absence of pathogens (Heidel et al 2004) and that normal pathogen-inducible SA-dependent defenses may be beneficial to plants under pathogen pressure (Heidel and Dong 2006). Our results in this work, together with similar results from others, suggest that activation of the SA-dependent defenses in plants is costly and thus R genes as triggers at the top of the signaling pathway are under stringent selection to balance the fitness benefits and costs associated with the expression of the R genes according to the temporally and spatially variable physical and pathogen environments.…”
Section: Discussionsupporting
confidence: 92%
“…Detection of hypersensitive response-like cell death ( Figure 7D) and PR1 expression in leaves of 6-weekold plants of S5 and the naturally RPW8-expressing accession Ms-0 grown in soil in the absence of any pathogens, along with the observation that enhanced RPW8 expression leads to spontaneous cell death and reduced plant size (Xiao et al 2003) strongly supports our speculation that reduced fitness in the RPW8 transgenic lines was due to RPW8-expression-triggered constitutive activation of an SA-dependent defense pathway under certain environmental conditions. This is consistent with the recent observations that constitutive activation of the SA-dependent defenses in several A. thaliana mutants incurred fitness costs in the absence of pathogens (Heidel et al 2004) and that normal pathogen-inducible SA-dependent defenses may be beneficial to plants under pathogen pressure (Heidel and Dong 2006). Our results in this work, together with similar results from others, suggest that activation of the SA-dependent defenses in plants is costly and thus R genes as triggers at the top of the signaling pathway are under stringent selection to balance the fitness benefits and costs associated with the expression of the R genes according to the temporally and spatially variable physical and pathogen environments.…”
Section: Discussionsupporting
confidence: 92%
“…S7), AED1 might be part of a homeostatic mechanism to limit SAR signaling (Fig. 7) and thus regulate the resource allocation in the tradeoff between defense and plant growth (Heidel and Dong, 2006;van Hulten et al, 2006;Traw et al, 2007;Pajerowska-Mukhtar et al, 2012). In support of this, we found that reduced AED1 transcript levels in Arabidopsis RNAi:AED1/At5g10770 plants caused severe stunting, a phenotype that is often observed in constitutive defense mutants (Shirano et al, 2002; Figure 7.…”
Section: Discussionsupporting
confidence: 67%
“…A recent field study confirmed that SAR increases the fitness of plants exposed to pathogens, which translates into enhanced crop yield [52]. However, unlike the fitness cost of constitutive resistance that associated with inducible resistance generally appears to outweigh the cost of pathogen infection, although this might depend on additional environmental factors [53,54 ]. In the era of metabolomics, large-scale surveys might reveal additional candidate compounds involved in SAR induction (e.g.…”
Section: Signal Perception and Amplificationmentioning
confidence: 99%